Analysis for water conflict transformation. Issue 4 (18th May 2020) - Zeitoun, Mark; Mirumachi, Naho; Warner, Jeroen; Kirkegaard, Matthew; Cascão, Ana
ABSTRACT: This article proposes and fleshes out an analytical method designed to support efforts to transform inequitable and unsustainable transboundary water arrangements. Such 'transformative analysis' leverages socio-ecological thinking to critically evaluate the processes that have established and maintain an arrangement, including hydro-diplomacy itself. Transformative analysis facilitates the interpretation of strategies to deflect transformation, identification of destructive forms of cooperation, and strategic classification of opportunities for transformation. The assertions are premised on an understanding of the particularities of water conflict, and followed by a discussion of ways researchers may overcome the challenges inherent in the method.